2014
DOI: 10.1177/1741143214535747
|View full text |Cite
|
Sign up to set email alerts
|

The use of technology in Prince Edward Island (Canada) high schools

Abstract: The purpose of this paper is to document the perceptions of school leaders regarding the technological use, skills, and attitudes of high school teachers. Using a qualitative research approach, 11 educational leaders from Prince Edward Island (Canada) were individually interviewed. Participants represented the Department of Education, principals, vice-principals, and department heads. Analyzed through the concept of e-leadership, the findings indicated that participants used a growing array of technological to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
(15 reference statements)
2
7
0
7
Order By: Relevance
“…Cox and McLeod (2014a) showed that publicly sharing and communicating the school's vision was perceived as a benefit. Preston et al (2015) were more critical: they concluded that for education to renew in the direction of digital teaching, school boards should acknowledge and recognise this goal, and incorporate it in plans for improvement. Social media can help to share this goal and vision with stakeholders (cf.…”
Section: Educational Vision and Policy On Curriculum Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cox and McLeod (2014a) showed that publicly sharing and communicating the school's vision was perceived as a benefit. Preston et al (2015) were more critical: they concluded that for education to renew in the direction of digital teaching, school boards should acknowledge and recognise this goal, and incorporate it in plans for improvement. Social media can help to share this goal and vision with stakeholders (cf.…”
Section: Educational Vision and Policy On Curriculum Materialsmentioning
confidence: 99%
“…Whatever its form, teacher professional development was shown to be a significant predictor of the integration of Web 2.0 in schools (Pan & Franklin, 2011). However, when applying the plan in practice, lack of time on the teacher side could be a barrier (Preston et al, 2015).…”
Section: Professional Development For Using Social Mediamentioning
confidence: 99%
“…Through a critical perspective of CAS-integrated policies into the Danish upper secondary school, Jankvist and Misfeldt [8] discussed that "a strong reliance on CAS provides new and efficient procedural solution strategies to classical problems" (p. 19 According to this three-stage concept development, while during interiorization, learners become familiar with processes and operations on lower-level mathematical objects and eventually gain skills with these operations, in the stage of condensation learners "squeeze" the sequences of operations and are more able to think of the process as a whole rather than a series of steps. At this stage, learners are able to make comparisons, combine processes, and generalize.…”
Section: Opportunities In Using Dynamic Software In Math Educationmentioning
confidence: 99%
“…Findings of a study conducted in Prince Edward Island (Canada) indicate that a wide range of technological tools and activities such as smartboards, computer programs, educational applications, Prezi, flipped classrooms, and teacher blogs are currently used in high schools in Canada. [19] While teaching and learning of mathematics, among other subject matters, is often considered to be a tough and complicated cognitive endeavor [4], at the same time it has a high practical value in other scientific and technological fields [16]. Much research has been conducted to acknowledge the supportive effects of using instructional tools, such as a graphing calculator, Computer Algebra System (CAS), and Chartworld, in improving teaching and learning of mathematics [1,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Through a critical perspective of CAS-integrated policies into the Danish upper secondary school, Jankvist and Misfeldt [8] discussed that "a strong reliance on CAS provides new and efficient procedural solution strategies to classical problems" (p. 19) that sometimes lead to black-boxing of central concepts of the subject taught in the classroom. Through a theoretical lens, Jankvist and Misfeldt attempted to explain how using CAS in upper secondary school may cause misconceptions or learning difficulties in constructing and developing mathematical concepts.…”
Section: Opportunities In Using Dynamic Software In Math Educationmentioning
confidence: 99%